Retroperitoneal liposarcoma of the intestine: a rare cause of acute abdomen - Tiwari, Vikash C.; Mudhale, Vaibhav; Sharang, Kulkarni S.; Nyamagoud, Jineshwar; Srividya, Malluru (International Surgery Journal, 2021)
Retroperitoneal liposarcoma is a rare malignant mesenchymal tumor with an incidence of 2.5 per million individuals. It is usually asymptomatic until its large enough to compress the surrounding organs, so its early diagnosis is difficult. In current case a 41 year old male patient with no significant past medical history presented to emergency department with sudden onset of abdominal pain in the left lumbar region. On examination, the abdomen was distended, guarding and rigidity present with tenderness to palpation in the left lumbar region, and no mass was palpated. Abdominal USG revealed a large heterogeneous mass in the left lumbar region. As the origin of the mass was uncertain, the patient was evaluated with CECT of the abdomen which revealed a retroperitoneal mass highly s/o liposarcoma. Given the suspicion of a liposarcoma, the patient underwent an abdominal exploration and there was a retroperitoneal mass of 12x8 cm adherent to the left colon. Wide resection of this mass was done along with left colectomy and the specimen was sent for examination. The histopathology study determined lipomatous tumor well differentiated retroperitoneal liposarcoma. Retroperitoneal liposarcoma is a malignant tumor whose treatment is fundamentally surgical. These tumors tend to be resistant to radiotherapy and/or chemotherapy. Among the most important prognostic factors related to survival is surgery with non-affected margins.